2020
DOI: 10.1038/s41598-020-62825-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new Corvis ST parameters in normal, Post-LASIK, Post-LASIK keratectasia and keratoconus eyes

Abstract: The aim of this study was to evaluate the distribution of new Corneal Visualisation Scheimpflug technology (corvis St) parameters in normal, post-laser in situ keratomileusis (LASiK), post-LASiK keratectasia (Ke) and keratoconus (Kc) eyes, and explore the diagnostic ability of these parameters in distinguishing KE from LASIK eyes. Twenty-three normal eyes, 23 LASIK eyes, 23 KE eyes and 23 KC eyes were recruited in this study. the following new corvis St parameters were measured: Max inverse Radius, deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…This prospective study was conducted between September 2018 and January 2020. Clinical KC in current study was diagnosed according to the following criterion: (1) corneal topography revealing an asymmetrical bowtie pattern with or without skewed axes; (2) KC sign on slit-lamp examination, such as localized stromal thinning, conical protrusion, Vogt’s striae, Fleischer’s ring, or anterior stromal scar; (3) Belin Ambrosio enhanced ectasia total deviation index (BAD-D) value > 2.6 1 , 13 . The SKC eye in the current study was defined by (1) no clear evidence of KC in one eye; (2) the contralateral eye diagnosed with clinical KC eye 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prospective study was conducted between September 2018 and January 2020. Clinical KC in current study was diagnosed according to the following criterion: (1) corneal topography revealing an asymmetrical bowtie pattern with or without skewed axes; (2) KC sign on slit-lamp examination, such as localized stromal thinning, conical protrusion, Vogt’s striae, Fleischer’s ring, or anterior stromal scar; (3) Belin Ambrosio enhanced ectasia total deviation index (BAD-D) value > 2.6 1 , 13 . The SKC eye in the current study was defined by (1) no clear evidence of KC in one eye; (2) the contralateral eye diagnosed with clinical KC eye 17 .…”
Section: Methodsmentioning
confidence: 99%
“…With the software updated (number: 1.5r1902), new parameters were gradually used in the clinic 12 . Our previous studies found that new Corvis ST parameters were different between KC and normal control eyes 12 , 13 . Several studies have also reported that new Corvis ST parameters of SKC eyes are different from normal and KC eyes 14 , 15 .…”
Section: Introductionmentioning
confidence: 92%
“…The inclusion criteria of clinical KC were as follows 7 , 19 : asymmetric bowtie pattern with or without skewed axes revealed by corneal topography and at least one KC clinical sign detected by slit-lamp examination (localized stromal thinning, Vogt’s striae, Fleischer’s ring, conical protrusion, or anterior stromal scar). Unilateral KC was considered if a patient had KC in one eye but did not meet the diagnostic criteria in the contralateral eye.…”
Section: Methodsmentioning
confidence: 99%
“…The Corvis ® ST device (Oculus Optikgeräte GmbH; Wetzlar, Germany) is a non-contact tonometer system with an ultra-high-speed Scheimpflug camera that provides corneal biomechanical parameters and IOP information [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. It also affords a high degree of repeatability [ 13 , 25 , 26 , 27 ] and gives a correlation between age, corneal thickness, IOP, and some Corvis ® ST biomechanical parameters [ 17 , 24 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show differences in biomechanical Corvis ® ST parameters between keratoconic and healthy corneas [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. More recently, other studies have evaluated SCKC with this device [ 12 , 18 , 19 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%